Evidence for Increased Susceptibility to Breast Cancer From Exposure to Ionizing Radiation Due to a Familial History of Breast Cancer: Results From the Swedish Hemangioma Cohort. Issue 1 (31st July 2020) - Eidemüller, Markus; Holmberg, Erik; Lundell, Marie; Karlsson, Per
Abstract: Women with a history of breast cancer among family members are at increased risk for breast cancer. However, it is unknown whether a familial breast cancer history (FBCH) also increases individual susceptibility to breast cancer from radiation exposure. In this cohort study, 17, 200 female Swedish hemangioma patients with 1, 079 breast cancer cases diagnosed between 1958 and 2013, exposed to ionizing radiation in infancy, were linked to their first-degree relatives. The association between FBCH and radiation-induced breast cancer risk was assessed. Further, the relevance for breast cancer radiotherapy and mammography screening was evaluated. On average, the radiation-induced excess relative risk and excess absolute risk of breast cancer at age 50 years were 0.51 Gy −1 (95% confidence interval (CI): 0.33, 0.71) and 10.8 cases/10, 000 person-years/Gy (95% CI: 7.0, 14.6), respectively. Radiation risk was higher by a factor of 2.7 (95% CI: 1.0, 4.8; P  = 0.05) if 1 first-degree relative was affected by breast cancer. For whole-breast standard radiotherapy at age 40 years with a contralateral breast dose of 0.72 Gy, the 20-year radiation-related excess risk of contralateral breast cancer was estimated to increase from 0.6% for women without FBCH to 1.7% for women with FBCH. In a biennial mammography screening program at ages 40–74 years, radiation risk up to age 80 years would increase from 0.11% for women without FBCH to 0.29% for women with FBCH.